Stent-assisted coiling vs. coiling alone of ruptured tiny intracranial aneurysms: A contemporary cohort study in a high-volume center - Zhang, Guanghao; Wu, Yina; Wei, Yanpeng; Xue, Gaici; Chen, Rundong; Lv, Nan; Zhang, Xiaoxi; Duan, Guoli; Yu, Ying; Li, Qiang; Xu, Yi; Huang, Qinghai; et al. (Frontiers in Neurology, 2022)
Objective This study aims to compare the safety and efficacy of stent-assisted coiling (SAC) with those of coiling alone (CA) for the treatment of ruptured tiny intracranial aneurysms. Methods We enrolled 245 patients with ruptured tiny intracranial aneurysms treated with coil embolization. Patients were grouped into SAC and CA groups. Baseline characteristics, periprocedural complications, clinical outcomes, and angiographic results were compared between the two groups. In addition, a subgroup analysis was conducted in the SAC group, and patients were regrouped into low-profile visualized intraluminal support (LVIS) and laser-cut groups to compare the perioperative procedure-related complications and clinical and angiographic follow-up outcomes. Results All baseline characteristics were equivalent between the two groups except for aneurysm size and dome-to-neck aspect ratio. The rates of overall procedure-related complications, intraprocedural rupture, postoperative early rebleeding, intraprocedural thrombosis, postprocedural thrombosis, and procedure-related mortality were comparable between the two groups (P = 0.105, 0.145, 0.308, 1.000, 1.000, 0.160, respectively). Nevertheless, the rate of hemorrhagic complication in the SAC group was significantly higher (P = 0.023). The angiographic follow-up outcomes showed that the SAC group had a higher complete occlusion rate and lower recurrence rate (88.2 vs. 67.1%, 5.4 vs. 15.2%, P = 0.001). The clinical outcomes at discharge and follow-up between the two groups demonstrated no significant differences (P = 0.192 and P = 0.085, respectively). For subgroup analysis, LVIS stents were associated with a significantly higher rate of complete occlusion (P = 0.014) and a lower rate of intraprocedural rupture (p = 0.021). Moreover, multivariate analysis showed that there were no predictors for the overall, hemorrhagic, and ischemic procedure-related complications, while Raymond class was an independent predictor of retreatment (OR = 3.508, 95% CI 1.168–11.603; P = 0.029). Conclusion Stent-assisted coiling may increase the incidence of hemorrhagic events with favorable angiographic results and comparable clinical outcomes compared with stand-alone coiling. Nevertheless, LVIS stent could improve the safety compared with lazer-cut stent. Simultaneously, considering the better long-term effect, LVIS stent-assisted coiling may be a preferable choice for ruptured tiny intracranial aneurysms.